1999
DOI: 10.1097/00003643-199903000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Minimum alveolar concentration of sevoflurane that blocks the adrenergic response to surgical incision in women: MACBAR

Abstract: a positive response. The probability of no response Summary to stress was analysed using logistic regression to We have investigated the cardiovascular and plasma obtain the probability of no response vs. end-tidal noradrenaline response to surgical incision under sesevoflurane concentration and the best-fit curve from voflurane anaesthesia and determined the end-tidal the maximum likelihood estimators of the model paraconcentration of sevoflurane that blocks the admeters. MAC BAR (mean±SE) was 8.0±0.2%, MAC B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Thus we terminated any attempt to maintain anesthesia without sufentanil to avoid intraoperative awareness. This is in accordance with the study of Ura et al [10], who found that MAC BAR of single sevoflurane was as high as 8%.…”
Section: Figuresupporting
confidence: 93%
“…Thus we terminated any attempt to maintain anesthesia without sufentanil to avoid intraoperative awareness. This is in accordance with the study of Ura et al [10], who found that MAC BAR of single sevoflurane was as high as 8%.…”
Section: Figuresupporting
confidence: 93%
“…In contrast, MAC BAR of halothane in cats was 1.5 MAC (Schmeling et al. 1999), and the sevoflurane MAC BAR in women was surprisingly high at 3.5 MAC (Ura et al. 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MAC BAR of isoflurane in cats was only 1.1 MAC . In contrast, MAC BAR of halothane in cats was 1.5 MAC (Schmeling et al 1999), and the sevoflurane MAC BAR in women was surprisingly high at 3.5 MAC (Ura et al 1999). The remaining studies in human patients include the use of nitrous oxide in combination with various inhalational agents and report MAC BAR values ranging from 0.95 (Yasuda et al 1991) to 2.7 MAC (Nakata et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The esophageal temperature was measured using an electric thermometer probe placed orally into the thoracic esophagus. According to the previous reports [28, 31,32,33], a commercially available adaptor (Air way adaptor L-shape, Omron Colin Co., Ltd.) modified with an 8-Fr feeding tube (Atom Indwelling Feeding Tube, Atom medical Co., Ltd., Tokyo, Japan) was placed at the Y-piece of the breathing circuit. The feeding tube passed through the endotracheal tube so that its tip rested in the thoracic portion of the trachea.…”
Section: Methodsmentioning
confidence: 99%